Methodology of development of the methodological culture of the future teachers of natural disciplines in the process of professional preparation - Лаврентьєва, Олена (Pedagogy of Higher and Secondary Education, 2014)
Lavrentyeva O. А. Methodology of development of the methodological culture of the future teachers of natural disciplines in the process of professional preparation. The substantive conceptual provisions of the methods of development of the Science teacher’s methodological culture is shown in the article. Science teacher’s methodological culture and this phenomenon is given both broad and narrow interpretations according to the level of a teacher’s methodological activity formation. A specific educative way of thinking is determined as a system-forming factor of the methodological culture. Methodics is presented as a well-organized totality of algorithms, procedures, stages, complex of pedagogical terms, forms, facilities and receptions, forms and types of professionally-pedagogical training process, that are aimed at the end to provide general and special methodological training, on purposeful development for the future Sciences teacher of methodological culture.